PENGARUH PROFITABILITAS, KEPUTUSAN INVESTASI, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN (Manajemen & Bisnis Jurnal, 2022)
Abstract Property and real estate is a business sector that is engaged in the provision of land used for homes as well as tourism spots that have the necessary infrastructure. In establishing a company, of course, the main goal that needs to be achieved is the welfare of the company's shareholders. Maximizing the value of the company is an effort that can be done in achieving company goals. Maximizing the value of the company is a reflection of a value from a business entity that can be known through the value of the stock price used by investors as an assessment before investing in the company. The purpose of this study is to examine the effect of profitability (ROE), investment decisions (PER) and capital structure (DER) on firm value (PBV) in the property and real estate industry. The property and real estate industry listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period as the population used in the study, with a total sample income of 32 industries in the property and real estate business sector, where it is sourced and taken using several methods one of them is purposive sampling method. The analytical method used is multiple linear regression using the SPSS application. This study shows that the results of the impact on profitability (ROE) and capital structure (DER) have an impact and also have a significant positive effect on firm value. Meanwhile, investment decisions have a positive but not significant impact on firm value.